2022
DOI: 10.1515/ijfe-2022-0126
|View full text |Cite
|
Sign up to set email alerts
|

Novel zero waste tactics for commercial vegetables – recent advances

Abstract: Commercial vegetables include tomatoes, potatoes, onions, and eggplant due to their surplus production, availability, and affordability. The valorisation of the massive wastage of commercial vegetables and providing a long-term solution has been challenging. The review addresses the implications of biowastes on the environment and fosters the recent investigations into valorising commercial vegetable waste to develop multiple value-added products. It discussed the outcomes of the multiple technologies, majorly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 154 publications
0
2
0
Order By: Relevance
“…The agri‐food sector is a primary pool of plant‐derived side‐streams, which result from plant tissue processing and may include, but not limited to, leaves, stems, roots, seeds, and peels. Such materials may be regularly disposed, although they contain a spectrum of precious phytochemicals, which could be effectively recovered by deploying suitable techniques (Srenuja et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The agri‐food sector is a primary pool of plant‐derived side‐streams, which result from plant tissue processing and may include, but not limited to, leaves, stems, roots, seeds, and peels. Such materials may be regularly disposed, although they contain a spectrum of precious phytochemicals, which could be effectively recovered by deploying suitable techniques (Srenuja et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that waste material, such as the shells of nuts [22] or onion peels [23], can be used in the production of bio composite films with improved mechanical properties. Numerous studies have been conducted focusing on the extraction of bioactive compounds from fruit and vegetable waste streams, mostly on a small scale but with clearly demonstrated applications in both the food industry and cosmetic industry [19,[24][25][26][27][28][29][30][31][32][33][34][35]. However, due consideration should be given to the cost of setting up biorefineries or purchasing new equipment for the extraction of functional ingredients from side-streams remaining after normal processing, as costs may be prohibitive [19,31,36].…”
Section: Introductionmentioning
confidence: 99%